IMPLEMENTASI PROGRAM PEMBERDAYAAN PEREMPUAN KORBAN KEKERASAN DALAM RUMAH TANGGA DI KOTA BOGOR - Laura Fitriani Ibrahim; G Goris Seran; Ginung Ginung Pratidina (LPPM Universitas Djuanda Bogor, 2019)
The aims of the research are to describe the implementation of the program of empowering domestic violence victim women in Bogor City, to identify the supporting and inhibiting factors in implementing the program of empowering domestic violence victim women in Bogor City, and to recommend the solutions for solving the problems faced in implementing the program of empowering domestic violence victim women in Bogor City. This research uses qualitative method of research that produces descriptive data in the form of written words or oral from the people and behavior that can be observed. The results of this study indicate that the program for improving the quality of life and empowerment of women victims of domestic violence at Integrated Service Center of Women and Children Empowerment in Bogor City that is: awareness stage, problem analysis phase, phase priority problem determination, phase of finding problem solving, stage of implementing real action and evaluation phase. The problems faced by the victims who are less cooperative, limitations of the councellor in terms of quantity and time provided and facilities and infrastructure are still inadequate.Keywords: Domestic Violence, Women Empowering.